Verbgrammatikk i islandske tospråklige ordbøker med islandsk som kildespråk - Jónsson, Jón Hilmar (LexicoNordica, 1995)
This paper describes how information on Icelandic syntax appears in the entries for verbs in some of the more important of bilingual Icelandic dictionaries, i.e. whether syntactic information is given explicitly or expected to be deduced from examples. The interplay of syntactic and semantic features in the microstructure of the dictionaries is also looked at. The conclusion is that the syntactic description of verbs in bilingual Icelandic dictionaries is in many ways primitive, largely due to insufficient distinction between syntactic constructions, collocations, examples, and phrasal entries in the dictionary texts. These factors are appraised, taking other lexicographic traits in the dictionaries into account, and considered in the perspective of the state of the art of lexicography in Iceland in general.